Connecting structure subject to a variable load - CORNELIS. STINIS (2006)
The invention relates to a connecting structure (10) subject to a variable load, like a twist-lock for a container crane, comprising a connecting element (14) and an anchoring member (15) supporting the connecting element (14), the connecting element (15) and the anchoring member each comprising primary and secondary contact surfaces (22, 23, 30, 31), the primary contact surfaces (22, 23) engaging each other during use and the secondary surfaces (30, 31) being spaced apart during use but engaging each other upon deformation of the connecting element (14) and/or the anchoring member (15). In this way a secure connection is guaranteed over a long lifespan, and failure of the connecting structure may be anticipated in good time.